Dicarbonyl Stress and Glyoxalase-1 in Skeletal Muscle: Implications for Insulin Resistance and Type 2 Diabetes - Mey, Jacob T.; Haus, Jacob M. (Frontiers in Cardiovascular Medicine, 2018)
Glyoxalase-1 (GLO1) is a ubiquitously expressed cytosolic protein which plays a role in the natural maintenance of cellular health and is abundantly expressed in human skeletal muscle. A consequence of reduced GLO1 protein expression is cellular dicarbonyl stress, which is elevated in obesity, insulin resistance and type 2 diabetes (T2DM). Both in vitro and pre-clinical models suggest dicarbonyl stress per se induces insulin resistance and is prevented by GLO1 overexpression, implicating a potential role for GLO1 therapy in insulin resistance and type 2 diabetes (T2DM). Recent work has identified the therapeutic potential of novel natural agents as a GLO1 inducer, which resulted in improved whole-body metabolism in obese adults. Given skeletal muscle is a major contributor to whole-body glucose, lipid and protein metabolism, such GLO1 inducers may act, in part, through mechanisms in skeletal muscle. Currently, investigations examining the specificity of dicarbonyl stress and GLO1 biology in human skeletal muscle are lacking. Recent work from our lab indicates that dysregulation of GLO1 in skeletal muscle may underlie human insulin resistance and that exercise training may impart therapeutic benefits. This minireview will summarize the existing human literature examining skeletal muscle GLO1 and highlight the emerging therapeutic concepts for GLO1 gain-of-function in conditions such as insulin resistance and cardiometabolic disease.